2020
DOI: 10.1111/pce.13868
|View full text |Cite
|
Sign up to set email alerts
|

The HY5 and MYB15 transcription factors positively regulate cold tolerance in tomato via the CBF pathway

Abstract: The induction of C-repeat binding factors (CBFs) is crucial for plant survival at low temperatures. Therefore, understanding the mechanisms that regulate CBF transcription is vital for the future development of crops with increased cold tolerance. Here, we provide evidence for the existence of a LONG HYPOCOTYL 5 (HY5)-MYB15-CBFs transcriptional cascade that plays a crucial role in the cold response in tomato. The exposure of tomato plants to cold (4 C) increased the levels of HY5, MYB15 and CBFs transcripts. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 60 publications
1
34
0
Order By: Relevance
“…The environment worldwide is changing, with changes in temperature and humidity that significantly affect plant growth and development. Temperature is one of the important factors that limits the geographic distribution of organisms, and the tolerance to cold stress depends on their efficiency of physiological and cellular signal transduction mechanisms (Gao et al., 2020; Hajihashemi et al., 2020; Zhang et al., 2020). Low temperature has undesirable effects on plant morphogenesis (Sohag et al., 2020), while high humidity exacerbates such detrimental effects (Han et al .…”
Section: Discussionmentioning
confidence: 99%
“…The environment worldwide is changing, with changes in temperature and humidity that significantly affect plant growth and development. Temperature is one of the important factors that limits the geographic distribution of organisms, and the tolerance to cold stress depends on their efficiency of physiological and cellular signal transduction mechanisms (Gao et al., 2020; Hajihashemi et al., 2020; Zhang et al., 2020). Low temperature has undesirable effects on plant morphogenesis (Sohag et al., 2020), while high humidity exacerbates such detrimental effects (Han et al .…”
Section: Discussionmentioning
confidence: 99%
“…Qiu et al obtained SlHY5 frameshift mutated and found that the anthocyanin content in the mutant was lower than that in wild-type tomato 20 . HY5 can improve plant cold tolerance through direct regulation of CBF or indirect regulation of MYB15 21 .Anthocyanins accumulation could be inhibited by Gibberellins at low temperature in plants, while the expression level of the gibberellin signaling pathway gene GA2ox1 showed HY5 -dependent 22 . In strawberry, HY5 - bHLH9 heterodimer formed to regulate light-dependent coloration and anthocyanin biosynthesis, suggesting that HY5 can be involved in plant anthocyanin metabolism by acting together with other genes 23 .…”
Section: Introductionmentioning
confidence: 99%
“…VvMYB15 was found to be transcriptional regulation of stilbene biosynthesis in grapevine ( Ciaffi et al, 2019 ). SlMYB15 has been found to be involved in the direct regulation of HY5 on CBF pathway and ultimate cold tolerance in tomato ( Zhang et al, 2020 ). And MYB15 has been found to be involved in regulating plant responses to environmental stresses, such as drought, salt, and cold, the lack of knowledge associated with the molecular regulatory mechanisms of VvMYB15 on anthocyanin accumulation in response to abiotic stress still needs further investigation.…”
Section: Discussionmentioning
confidence: 99%